Prevotella - Avila-Campos, Mario J.; Simionato, Maria R.L.; Gaetti-Jardim, Elerson [UNESP] (My University, 2011)
Anaerobic bacteria constitute members of the indigenous microbiota in humans and animals. Although these organisms do not usually cause disease, they have the capacity to take advantage of a weakened host's immune status (e.g., due to injury and immune-suppressing therapy) and can be involved in either mixed or monomicrobial infections.